A case of Sotos syndrome with 5q35 microdeletion and novel clinical findings - Kılıç, Esra; Ütine, Gülen Eda; Boduroğlu, Koray (The Turkish Journal of Pediatrics, 2013)
Sotos syndrome is a multiple anomaly syndrome characterized by pre- and postnatal overgrowth with advanced bone age, macrocephaly, developmental delay, and distinctive facial phenotype. Autosomal dominant mutations and deletions of the nuclear receptor set domain gene (NSD1), which is located at chromosome 5q35, are responsible for most of the cases. We describe a six-year old boy who had tall stature, macrocephaly, typical facial appearance, learning disability, megaloencephaly, corpus callosum dysgenesis, and colpocephaly. Although he had normal bone age, the diagnosis of Sotos syndrome was suspected with these clinical findings, and fluorescence in situ hybridization analysis of the patient showed a heterozygous deletion covering the NSD1 region in the 5q35 locus. A brief overview of the syndrome is presented.